Mapping of B-cell epitopes on the N- terminal and C-terminal segment of nucleocapsid protein from Crimean-Congo hemorrhagic fever virus - Moming, Abulimiti; Tuoken, Daerken; Yue, Xihong; Xu, Wanxiang; Guo, Rong; Liu, Dongliang; Li, Yijie; Hu, Zhihong; Deng, Fei; Zhang, Yujiang; Sun, Surong (PloS one, 2018)
Crimean-Congo hemorrhagic fever virus (CCHFV) is a tick-borne pathogen that causes severe disease in humans. CCHFV is widely distributed in more than 30 countries and distinct regions, which means that it poses a serious threat to human health. The nucleocapsid protein (NP) encoded by the CCHFV S gene is the primary detectable antigen in infected cells, which makes it an important viral antigen and a clinical diagnostic target. In this study, the modified biosynthetic peptide (BSP) method was used to identify the fine epitopes on the N- and C- terminals of NP from the CCHFV YL04057 strain using rabbit antiserum against CCHFV-NP. Nine epitopes were identified: E1a (178NLILNRGG185), E1b (184GGDENP189), E2 (352PLKWGKK358), E3 (363FADDS367), E4 (399NPDDAA404), E5a (447DIVASEHL454), E5b (452EHLLHQSL459), E6 (464SPFQNAY470) and E7 (475NATSANII482). Western blotting analysis showed that each epitope interacted with the positive serum of sheep that had been naturally infected with CCHFV. Amino acid sequence alignment between each epitope and their homologous proteins showed that they were almost 100% conserved among 12 CCHFV sequences from different lineages, except for epitopes E1a, E1b and E2. Three-dimensional structural modeling analysis showed that all identified epitopes were located on the surface of the NP "head" domain. This study identified fine epitopes on the N- and C- terminals of NP, which will increase the understanding of the structure and function of NP, and it could lay the foundation for the design and development of a CCHFV multi-epitope peptide vaccine and detection antigen.